Coaches` perceived pitfalls in delivering psychological skills training to high-level youth athletes in fencing and football - Boysen Feddersen, N.; Bygballe Keis, M. A.; Elbe, A.-M. (International Journal of Sports Science & Coaching, 2021)
The current study examined how two high-level coaches in fencing and football perceived the challenges that emerged during a three-month coach education programme aimed at them delivering psychological skills training to athletes. We used action research as the study design and collected data using observations, six semi-structured interviews, and one focus group. We analysed the data using a thematic content analysis. Our findings showed that the coaches struggled with role clarity. The psychological impact was that coaches struggled with identifying the borders between delivering psychological skills training as a part of their coaching and when to refer athletes to sport psychology experts. The coaches also suggested that gaining more knowledge in sport psychology allowed them to analyse the athletes. However, the coaches viewed this as a potential area for abusing trust in the coach-athlete relationship. We suggest that coach education programmes should include content on ethical dilemmas to safeguard against potential abuse of the coach-athlete relationship.